Proceedings of the 5th ASEAN Conference on Psychology, Counselling, and Humanities (ACPCH 2019) 2020
DOI: 10.2991/assehr.k.200120.058
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Emotional Intelligence in Adolescent Development

Abstract: This review presents accurate research results in complex adolescent literature and further clarifies that emotional intelligence is fundamental in adolescent development and has an essential role in developmental stages. 15 journals are used to review national and international publications from [2004][2005][2006][2007][2008][2009][2010][2011][2012][2013][2014][2015][2016][2017][2018]. Reviewed from gender differences, teenage boys have low levels of emotional intelligence than teenage girls. Emotions strongl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
5
0
3
Order By: Relevance
“…Thus, the awareness of its moderators is indispensable to save up costs to society (Fry et al, 2018;Fung, 2019). In this line, Emotional intelligence, which enables individuals to understand and manage their and others' emotions (Tziner et al, 2020), is closely linked to adolescents' development and welfare -especially when worked through school-based programmes, ye it seems to be gender-differences, with females presenting a higher emotional intelligence (Furqani, 2020). Likewise, self-concept has a pivotal role in individuals' well-being, which may help people to control their anxiety and cope with harmful situations (Bayrak et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the awareness of its moderators is indispensable to save up costs to society (Fry et al, 2018;Fung, 2019). In this line, Emotional intelligence, which enables individuals to understand and manage their and others' emotions (Tziner et al, 2020), is closely linked to adolescents' development and welfare -especially when worked through school-based programmes, ye it seems to be gender-differences, with females presenting a higher emotional intelligence (Furqani, 2020). Likewise, self-concept has a pivotal role in individuals' well-being, which may help people to control their anxiety and cope with harmful situations (Bayrak et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Delving into this negative association, reported a worse emotional intelligence in victims of aggression, as opposed to aggressors, who only show low levels of emotional regulation; these findings are in line with Cañas et al (2019), who found that whilst cybervictims tend to pay more attention to their emotions, non-cybervictims have greater emotional clarity and regulation. To conclude, a high emotional intelligence provides victims the capability to deal with aggressions (Nel, 2019), even reducing the possibilities of suicide (Rey et al, 2019) Additionally, self-concept is positively associated with emotional intelligence (Alviz et al, 2020;Cañas et al, 2020;Furqani, 2020), especially as for the physical and social self-concepts (Guerrero-Baona et al, 2019), and in terms of gendered self-concept -in which emotional attention is mostly predicted by feminine self-concept whilst emotional clarity and repair by both-(Martínez-Marín et al, 2020)-.…”
Section: Introductionmentioning
confidence: 99%
“…Factor 1: reconocimiento de las emociones (10 ítems, α = 0.82); factor 2: autorregulación conductual y cognitiva de las emociones (10 ítems, α = 0.81); factor 3: relaciones interpersonales (10 ítems, α = 0.85); factor 4: sensibilidad interpersonal (10 ítems, α = 0.87). Se utilizó el cuestionario Mesquite como estándar de oro y se observaron correlaciones entre reconocimiento de las emociones e inteligencia emocional moderada (7)(8)(9)(10)(11)(12)(13)(14)(15) (r = 0.753) p < 0.01), autorregulación conductual y cognitiva de las emociones e inteligencia emocional elevada (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) (r = 0.751) (p < 0.01). Sensibilidad interpersonal e inteligencia interpersonal moderada (7)(8)(9)(10)(11)(12)(13)(14)(15) (r = 0.791 p < 0.01).…”
Section: Introductionunclassified
“…Se utilizó el cuestionario Mesquite como estándar de oro y se observaron correlaciones entre reconocimiento de las emociones e inteligencia emocional moderada (7)(8)(9)(10)(11)(12)(13)(14)(15) (r = 0.753) p < 0.01), autorregulación conductual y cognitiva de las emociones e inteligencia emocional elevada (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) (r = 0.751) (p < 0.01). Sensibilidad interpersonal e inteligencia interpersonal moderada (7)(8)(9)(10)(11)(12)(13)(14)(15) (r = 0.791 p < 0.01). Las correlaciones test-retest en los ítems de la escala total oscilaron entre r = 0.76 y r = 0.82.…”
Section: Introductionunclassified
See 1 more Smart Citation